Numerical Study of Natural Convection of Magnetic Fluids in a Cubic Cavity with a Heat Generating Object Inside by the Lattice Boltzmann Method (Advances in Applied Mathematics and Mechanics, 2010)
In this article, natural convection of a magnetic fluid in a cubiccavity with a heat generating object inside and under a uniformmagnetic field is simulated by the lattice Boltzmann method. Resultsobtained from the present simulations are shown to agree wellwith our experimental measurements, and reveal more of effects ofthe magnetic field on the flow and heat transfer of the magneticfluids.